COGNITIVE MEDIATION OF DEPRESSED MOOD AND NEUROTICISM - Martin, M; Clark, D (1985)
One of the best predictors of the occurrence of clinical depression consists of a high score on the personality trait of neuroticism. We have proposed that this association is a consequence of similar idiosyncracies of cognitive processing in the two cases. The present work examined this proposal further. The subjects were 61 undergraduate women volunteers. Partial-correlation analysis showed that both depression and neuroticism were significantly associated with a tendency to attribute bad events to a composite group of internal, stable and global factors, and with a tendency to endorse negative characteristics as descriptive of the self.